Contradiction and mechanism analysis of science and technology input-output: Evidence from key universities in China - Cao, Qinwei; Qiu, Shunli; Huang, Jian (Socio-economic planning sciences, 2022)
In order to clarify the reasons for the input-output contradiction of S&T in China, based on the resource-based view (RBV), we subdivide the input-output data of key universities in China and carry out empirical research. The results showed that (1) the combination of different input-output indicators has complex heterogeneous relationship. If the differences among indicators are not taken into account, contradictory conclusions may be drawn. (2) Government investment has a greater positive impact on the innovation performance of universities than enterprise investment. (3) Basic research intensity only mediates fund investment and innovation performance, while there is no mediating role between human input and innovation performance. Theoretically, our research further extend the boundary of subjects and the connotation of resources heterogeneity in RBV. Practically, we suggest that universities should constantly improve the performance evaluation system, take full account of the difference between different types of input-output. Meanwhile, the government should strengthen the system construction and mechanism design, guide more talents to participate in basic research, especially increase the funding support for basic research. •We have analyzed the structural contradictions of S&T input-output from the perspective of universities.•We change input-output as the mainstream study of efficiency evaluation and explore the functional mechanism and boundary conditions of S&T input-output.•We construct a basic framework to analyzewhether and how to influence the S&T input-output in Chinese universities.